Pengaruh Struktur Kepemilikan, Dispersi Kepemilikan dan Struktur Modal Terhadap Kebijakan Deviden - Atiqah Ganjar; Usep Syaipudin; Niken Kusumawardani (Politeknik Negeri Lampung, 2023)
This study aims to determine: (1) The effect of ownership structure on the dividend policy of property companies listed on the IDX in 2015-2019, (2) The effect of dispersion of ownership on the dividend policy of property companies listed on the IDX in 2015-2019, (3) Effect of capital structure on dividend policy of property companies listed on the Indonesia Stock Exchange in 2015-2019. This type of research is quantitative research with secondary data. The population in this study were property companies listed on the Indonesia Stock Exchange in 2015-2019. The samples of this study were 10 property companies listed on the Indonesia Stock Exchange in 2015-2019. The data were obtained using the financial statements of property companies for the 2015-2019 period. The data analysis method used is multiple regression analysis. Based on the results, this study indicates that (1) the ownership structure has a positive effect on the dividend policy of property companies. (2) Dispersion of ownership does not affect the dividend policy of property companies. And (3) Capital structure has no effect on dividend policy of property companies.